Real research : research methods sociology students can use - Gordon, Liahna E. (Sage, 2020)
Real Research: Research Methods Sociology Students Can Use by Liahna Gordon is an innovative text that takes a holistic approach to the subject by discussing each step in the research process within the context of a particular method. With no generalizations about concepts that apply to only some research methods but not others, students can jump into the first research method within the first two weeks of class. After an overview of data collection in the first chapter, subsequent chapters focus on eight specific quantitative and qualitative methods most frequently used in sociology. The Second Edition includes a new chapter on focus groups, updated "Real Research" profiles of individuals using research methods in a wide range of careers, and examples of common student errors to streamline learning.